Web Based Spatial Query System for Decision Making (International Journal of Engineering and Computer Science, 2015)
GIS is becoming essential to understand what is happening and what will happen-in geographic space. This project web based geographic information system (GIS) lets us visualize, question, analyze, and interpret data to understand relationships, patterns, and trends online. Most of the geo-portals which are web based primarily provide display of geo-data/ satellite images. But analysis of geographical data to solve the problem of real nature on the move is very limited. The proposed project work envisages development of a prototype for carrying out multilayer GIS queries online using geo processing techniques and WPS. The development of this prototype is aimed at providing support in decision making to the users online. Through this model, users can query information of specific geographical area of interest from data spanning multiple layers. The query result will be retrieved by making use of geo-processing techniques, and Open Geo Consortium (OGC) compliant services such as Web Processing Service (WPS) and Web Map Service (WMS) etc. Spatial queries are also performed on the resultant output obtained by spatial queries performed earlier, thus forming a chain of web of processing services.